2009
DOI: 10.1007/s11661-009-0063-3
|View full text |Cite
|
Sign up to set email alerts
|

Functionally Graded Al Alloy Matrix In-Situ Composites

Abstract: In the present work, functionally graded (FG) aluminum alloy matrix in-situ composites (FG-AMCs) with TiB 2 and TiC reinforcements were synthesized using the horizontal centrifugal casting process. A commercial Al-Si alloy (A356) and an Al-Cu alloy were used as matrices in the present study. The material parameters (such as matrix and reinforcement type) and process parameters (such as mold temperature, mold speed, and melt stirring) were found to influence the gradient in the FG-AMCs. Detailed microstructural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 21 publications
0
14
0
3
Order By: Relevance
“…It is also observed that the mixture of particle sizes is useful in controlling the composition. Functionally graded aluminium in-situ composites with Titanium Diboride (TiB 2 ) and Titanium Carbide (TiC) reinforcements are fabricated using horizontal centrifugal casting method and found the segregation of reinforcements at the outer periphery, as this is due to stirring of molten metal before pouring into the die, while the absence of stirring caused the reinforcements to settle at the inner periphery of the casting [5]. The hardness of these composites increases with increase in volume fraction of reinforcement particles.…”
Section: Introductionmentioning
confidence: 99%
“…It is also observed that the mixture of particle sizes is useful in controlling the composition. Functionally graded aluminium in-situ composites with Titanium Diboride (TiB 2 ) and Titanium Carbide (TiC) reinforcements are fabricated using horizontal centrifugal casting method and found the segregation of reinforcements at the outer periphery, as this is due to stirring of molten metal before pouring into the die, while the absence of stirring caused the reinforcements to settle at the inner periphery of the casting [5]. The hardness of these composites increases with increase in volume fraction of reinforcement particles.…”
Section: Introductionmentioning
confidence: 99%
“…A. Sreenivasan (Sreenivasan, Vizhianb, Shivakumarc, Munirajua, & Raguramand, 2011) arkadaşları ile 6061 alaşımına %15 TiB2 ilavesiyle aşınma hızının önemli oranda azaldığını rapor etmişlerdir. S. Kumar (Kumar, Subramaniya Sarma, & Murty, 2010) and M. F. Forster (Forster, Hamilton, Dashwood, & Lee, 2003) ve arkadaşları TiB2 partilkül takviyeli fonksiyonel derecelendirilmiş alüminyum matrisli kompozitleri savurma döküm yöntemi ile ürettiklerini rapor etmişlerdir. Yapılan çalışmalarda takviye oranın savurma yönünde değiştiği ve kompozitlerin özelliklerinin yöne bağılı olarak değiştiğini belirmişlerdir.…”
Section: Introductionunclassified
“…The microstructure of the functionally graded composites is extremely controlled by the parameters such as density of reinforcement, matrix alloy, mold temperature, mold speed and also found that stirring of the molten metal before pouring controls the position of the reinforcement particles [4]. Investigation on the position and particle enriched region of the reinforcement has been made and reported that thickness of the reinforcement particles region depends upon rotational speed of the mold and also interpreted that casting/mold interface temperature decides the presence of particles at the outer periphery [5].…”
Section: Introductionmentioning
confidence: 99%